1998
DOI: 10.1093/her/13.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self-reported body weight: Stepped Approach Model component assessment

Abstract: This study was conducted to investigate innovative solutions to a measurement problem pertaining to self-reported body weight data as a key component of the Stepped Approach Model (SAM) of service delivery. Subjects (n = 223) were randomly assigned to one of two conditions: Informed Group (of self-report and weight measurement) + six body weighing habit items (IG, n = 113) and Uninformed Group (of self-report and weight measurement) + one body weight item (UG, n = 110). A t-test indicated that IG subjects repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
0
27
1
1
Order By: Relevance
“…Previous reports on bias in self-reported weight and height [9][10][11][12][13][14] had all been based on individual-level data. As a result, these works could not examine two factors important for population-level monitoring: first, individuallevel misreporting caused by absence of measurement subsequent/previous to the interview and by the mode of self-report, and second, differential participation based on the survey mode.…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on bias in self-reported weight and height [9][10][11][12][13][14] had all been based on individual-level data. As a result, these works could not examine two factors important for population-level monitoring: first, individuallevel misreporting caused by absence of measurement subsequent/previous to the interview and by the mode of self-report, and second, differential participation based on the survey mode.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Self-reported weight and height data are subject to random error, and, more importantly, systematic reporting bias. [9][10][11][12][13][14] The magnitude of bias has varied across studies based on factors such as age, actual weight and height, and education. 9 Some researchers have nonetheless concluded that self-reported height and weight are acceptable, valid, or excellent for population-based studies.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the prevalence of obesity based on self-report may be affected by bias toward lower BMI from underreporting of weight influenced by social desirability. 19,20 Of note, self-report adult BMI data from the PSID closely match other self-report data available from concurrent waves of the National Health Interview Survey. 21 Another limitation is that we assessed intrafamilial BMI associations at one point in time; future work will permit assessments of these relationships over longer periods.…”
Section: Commentmentioning
confidence: 64%
“…The underreporting bias may be mitigated in the present case because survey respondents answered the question about past weight after having been weighed. Black et al (1998) found that the accuracy of self-reported weight did not decrease as weight increased for individuals who knew they would have their weight measured following the weight survey. Moreover, as long as SNAP participants are not more or less likely than nonparticipants to underreport past weight, we can still consistently estimate the difference in weight gain between the two groups.…”
Section: Datamentioning
confidence: 94%